Effect of Organic Fertilizer on Growth and Physiology of Brachychiton populneus (Schott& Endl) Seedlings under Drought Conditions - Shaymaa Hani Mahmood; Sirwa Anwar Qadir; Evan Anaeat Mohammed; Chnar Najmaddin Fathulla; Aven Alaalddin Ahmed (Zanco Journal of Pure and Applied Sciences, 2024)
Drought stress negatively impacts plant growth and agricultural productivity. This study investigates whether organic fertilizer can mitigate these effects by improving the growth and physiological responses of Brachychiton populneus seedlings under drought conditions. Thus, local compost added to Brachychiton populneus (Schott & Endl) to determine whether it could aid the growth of the seedlings during drought conditions. Two drought stress levels (D1 and D2), or 60% and 30% of the soil water holding capacities (SWHC%), were applied to the seedlings compared to the control (C0). There were two additions of local compost (C1 and C2), 2000 and 4000 ppm, respectively, in comparison to the control treatments. D1C2 (soil water holding capacity of 60% and 4000 ppm compost) was the usual treatment combination. Which resulted in the longest shoot and root lengths. By registering the maximum dry matter content in the roots and shoots, the same combination also greatly increased the biomass of the seedlings. A general decline in the relative water content appears when biomass increases. The consequences of drought stress are lessened by the addition of compost, which also improves chlorophyll production and overall plant growth. Growth and physiological parameter correlations are shown by the component plot in rotated space. The highest variance is explained by component 1, and the second largest by component 2. A positive association was seen between root length, shoot height, and total dry weight, as they clustered together. Conversely, there is a negative association observed between the components of relative water content and shoot dry weight. However, component 2 and the leaf chlorophyll content (a, b, and total) showed a significant correlation. Compost provides a sustainable solution for improving drought resilience in Brachychiton populneus, making them crucial for forest nurseries and reforestation efforts in arid and semi-arid regions.